Moderating Effects of Social Value Orientation on the Effect of Social Influence in Prosocial Decisions - Wei, Zhenyu; Zhao, Zhiying; Zheng, Yong (Frontiers in Psychology, 2016)
Prosocial behaviors are susceptible to individuals’ preferences regarding payoffs and social context. In the present study, we combined individual differences with social influence and attempted to discover the effect of social value orientation and social influence on prosocial behavior in a trust game and a dictator game. Prosocial behavior in the trust game could be motivated by strategic considerations whereas individuals’ decisions in the dictator game could be associated with their social preference. In the trust game, prosocials were less likely than proselfs to conform to the behavior of other group members when the majority of group members distrusted the trustee. In the dictator game, the results of the three-way ANOVA indicated that, irrespective of the type of offer, in contrast to proselfs, prosocials were influenced more by others’ generous choices than their selfish choices, even if the selfish choices were beneficial to themselves. The overall results demonstrated that the effect of social influence appears to depend on individuals’ social value orientation: that is, prosocials tend to conform to prosocial rather than proself behaviors.